Strategy for Increasing Halal Tourism in the Indonesia Post-Pandemic Covid 19 - Arohman, Arohman; Haryono, Slamet (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Indonesia has the potential to become a globally popular halal tourist due to its large Muslim population and beautiful and diverse cultural attractions. However, during the COVID-19 pandemic, the country faced several challenges in developing this sector. Halal tourists continue to experience a decline due to foreign and domestic tourists not making visits by considering many factors, including health, the economy, and the attractiveness of tourist attractions. This study seeks to explore strategies for increasing halal tourism in Indonesia by using a SWOT analysis consisting of strengths, weaknesses, opportunities, and threats. After observing and analyzing, we present research results based on the SWOT sub-indicators. The first is strength. Indonesia has a rich cultural heritage, diverse and attractive natural resources, a large Muslim population, and the availability of many places of worship for Muslim tourists which can be utilized to develop halal tourism. The country also has a well-developed tourism infrastructure, with international airports, hotels, and a transportation system in major cities. Second, weakness. Despite its potential, Indonesia faces several challenges in developing halal tourism, such as the ongoing pandemic that endangers the safety of tourism, limited accessibility, problems with halal certification standards, and weak marketing. The third is opportunity. Indonesia can exploit the growing demand for halal tourism by developing targeted marketing using platform media, creating halal-friendly accommodations and services, and streamlining the halal certification process. The country can also take advantage of emerging trends such as ecotourism and adventure tourism to attract more tourists. Fourth, threats. Indonesia faces competition from other countries that are also investing in halal tourism, such as Malaysia and Turkey. The country also faces external threats such as political instability and the COVID-19 pandemic which can disrupt the halal tourism industry. Therefore, to overcome these challenges, Indonesia can develop a comprehensive strategy that focuses on improving halal certification standards, promoting halal-friendly accommodations and services, and creating optimal and targeted marketing to attract Muslim tourists. Governments can also invest in infrastructure development, such as expanding airports and transportation systems, to enhance the tourism experience.